The Effects of Corporate Governance on Company Performance and Dividends in Three Asean Countries - Werner Ria Murhadi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2021)
This study aims to investigate the effects of corporate governance on company performance and dividends paid by the company. In developing countries where the protection system against public investors is still weak, corporate governance becomes important. This study uses a sample of manufacturing companies in three developing countries. i.e., Indonesia, Malaysia, and Thailand. The variables that represent corporate governance are board characteristics and ownership structure. Board characteristics comprise board size, independent board, and board gender, while the ownership structure uses managerial ownership and institutional ownership. The results show that in Indonesia, corporate governance has no significant effect on company performance and dividends. In comparison, in Malaysia, the female board has a positive effect on both performance and dividends paid. Whereas in Thailand, institutional ownership has a negative effect both on performance and dividends paid. The results also consistently show that debt and company size have an effect on performance and dividends in the three countries.